Long-Term Effect of Allergen Immunotherapy in Responder Local Allergic Rhinitis Patients: Symptom Control, and Prevention of Asthma and Allergic Sensitizations - Testera Montes, Almudena; Zubiaga- Fernandez, L.; Aranda, Carlos José; García-Esteban, Irene; Gaitan-Nievas, Trinidad Ilda; Sánchez-Torralvo, Dulce; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa; Ibon Eguíluz, Gracia; Rondón Segovia, Carmen (Wiley, 2025)
Background: Clinical trials (CTs) have shown that allergen immunotherapy (AIT) is effective for local allergic rhinitis (LAR) while treatment is ongoing. However, its long-term effects remain unknown. This study investigates the long-term clinical and preventive effect of AIT in responder LAR patients. Methods: LAR patients obtaining a clinical benefit from 1-year CT of subcutaneous AIT were enrolled in this 10-year follow-up study (AIT cohort). All completed a full 3-year AIT course and were followed for additional 7 years. A matched group of LAR patients who did not receive AIT (non-AIT cohort) was followed over the same period. Primary outcomes included nasal-ocular symptom scores (visual analogue scale, VAS), reliever medication use and medication-free days (MFD). Secondary outcomes were asthma incidence, asthma control (asthma control test, ACT), lung function (FEV1), quality of life (QoL), emergency visits, new sensitizations detected by nasal allergen challenge (NAC), and the analysis of the minimal clinically important difference (MCID). Assessments were conducted at baseline and at years 1, 3, 5, 7, and 10. Results: Sixty-six patients were included (AIT n = 32; non-AIT n = 34). The AIT cohort showed a sustained reduction in nasal-ocular symptoms from year 1 (p < 0.001) and significantly more MFD from year 3 (p < 0.001). Asthma developed in 40.7% of non-AIT vs. 8.0% of AIT patients (p = 0.021). New sensitizations occurred in 38.2% of non-AIT and 6.3% of AIT patients (p = 0.002). FEV1 improved in the AIT cohort and declined in non-AIT (p < 0.001). QoL and emergency visits also favored AIT. Conclusion: AIT induces a sustained clinical improvement and prevents the onset of asthma and local sensitizations in responder LAR patients.
Keywords: inmunoterapia; asma; alergia; allergen immunotherapy; asthma; local allergic rhinitis; long-term effect; prevention